Reception Analysis on Sandwich Generation about Financial Literacy In Maudy Ayunda’s YouTube Video - Ramadhana, Ghivary Rizky; Putri, Berlian Primadani Satria (eProceedings of Management, 2024)
The sandwich generation phenomenon is prevalent in developing countries as family life is usually valued in thesecountries. One of the problems faced by the sandwich generation is financial literacy. Therefore, the purpose of thisstudy is to further analyse the Sandwich Generation's reception of Maudy Ayunda's content on financial literacy. Thedata analysis used in this research is Miles and Huberman's interactive analysis. In this study, researchers usedqualitative methods by interviewing 8 (eight) informants and used triangulation techniques. The theory used as atheoretical basis in this research is Stuart Hall's reception theory. Stuart Hall's Reception Analysis explains theexistence of 3 (three) coding in receiving a message; namely dominant hegemonic, negotiated, opposition. The resultsof this study found 2 (two) things, namely; First, Sandwich Generation is receiving the message from Maudy Ayunda'scontent <Sandwich Generation: Menanggung Biaya Hidup atau Gaya Hidup= regarding to the financial literacy. Thisacceptance is based on the message their accept and adds new insight. Second, the negotiation position, informant canaccept the messages but with different points of view. In this study, researcher did not find the coding of oppositioninformants. Keywords-reception analysis, sandwich generation, financial literacy, YouTube